State of the Arctic Marine Biodiversity Report - Conservation of Arctic Flora and Fauna (CAFF) (Conservation of Arctic Flora and Fauna, 2017)
The Arctic Biodiversity Assessment (ABA) (Meltofte 2013) provides the fundamental baseline to make trend assessments in SAMBR possible. Six Marine Expert Networks (Sea ice biota, Plankton, Benthos, Fishes, Seabirds and Marine mammals) provide the framework to implement the CBMP Marine Plan and generate the information required for SAMBR. This State of the Arctic Marine Biodiversity Report (SAMBR) is the first integrated reporting outcome from the Circumpolar Biodiversity Monitoring Program (CBMP). The Arctic Biodiversity Assessment (ABA) (Meltofte 2013) provides the fundamental baseline to make trend assessments in SAMBR possible. Six Marine Expert Networks (Sea ice biota, Plankton, Benthos, Fishes, Seabirds and Marine mammals) provide the framework to implement the CBMP Marine Plan and generate the information required for SAMBR.